Focused ultrasound robotic system for very small bore magnetic resonance imaging. Issue 6 (22nd September 2020) - Damianou, Christakis; Giannakou, Marinos; Evripidou, Nikolas; Kegel, Stefan; Huber, Peter; Jenne, Juergen
Abstract: Background: A magnetic resonance imaging (MRI) compatible robotic system for focused ultrasound was developed for small animal like mice or rats that fits into a 9.4 T MRI scanner (Bruker Biospec 9420, Bruker Biospin, Ettlingen, Germany). The robotic system includes two computer‐controlled linear stages. Materials and Methods: The robotic system was evaluated in a mouse‐shaped, real‐size agar‐based mimicking material, which has similar acoustical properties as soft tissues. The agar content was 6% weight per volume (w/v), 4% w/v silica while the rest was degassed water. The transducer used has a diameter of 4 cm, operates with 2.6 MHz and focuses energy at 5 cm. Results: The MRI compatibility of the robotic system was evaluated in a 9.4 T small animal scanner. The efficacy of the ultrasonic transducer was evaluated in the mimicking material using temperature measurements. Conclusions: The proposed robotic system can be utilized in a 9.4 T small animal MRI scanner. The proposed system is functional, compact and simple thus providing a useful tool for preclinical research in mice and rats.